Analisis Faktor-faktor Risiko Kejadian Penyakit Jantung Koroner di Rumah Sakit Ibnu Sina Makassar Tahun 2021 - Dahliah Dahliah; Prema Hapsari Hidayati; Wisudawan Wisudawan; M. Iswan Wahab; Afifah Ridha Humairah (Syntax Idea)
In Indonesia, Coronary Heart Disease (CHD) is the main cause of all deaths. Risk factors that contribute to the occurrence of coronary heart disease are divited into risk factors that cannot be changed, namely age, sex, and heredity, and risk factors that can be changed, namely dyslipidemia, hypertension, obesity, and diabetes mellitus. To describe the risk factors for coronary heart disease at the Ibnu Sina Hospital in Makassar in 2021. The type of research used is a descriptive retrospective study using a cross-sectional design based on secondary data from medical records at Ibnu Sina Hospital Makassar in 2021. The highest CHD incidence based on the types was Stable Angina Pectoris (SAP) with 45 people (53.3%) and the most risk factors were in the late elderly group (56-65 years) with 26 people (31.0%), male sex with 57 people (67.9%), hypertension stage 1 with 37 people (44.0%), not accompanied by diabetes mellitus with 68 people (81.0%), and accompanied by dyslipidemia with 46 people (54.8%). CHD patient are most commonly found with a diagnosis of SAP, the late elderly group (56-65 years), male, stage 1 hypertension, not accompanied by diabetes mellitus, and accompanied by dyslipidemia.